2016
DOI: 10.1111/liv.13124
|View full text |Cite
|
Sign up to set email alerts
|

Hepcidin resistance in dysmetabolic iron overload

Abstract: Dysmetabolic iron overload syndrome is associated with a subtle impairment in the ability of the iron hormone hepcidin to restrain iron absorption following an iron challenge, suggesting a hepcidin resistance state. Further studies are required to better characterize the molecular mechanism underpinning this new iron metabolism alteration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 46 publications
1
9
0
2
Order By: Relevance
“…Also, bone morphogenic protein-binding endothelial regulator [ 34 ] and hepatocyte nuclear factor-4alpha [ 35 ] have been reported to influence iron absorption, and in mice, a high fat diet by itself could increase iron absorption [ 36 ]. An impairment in the ability of hepcidin to inhibit iron absorption was demonstrated in DIOS, suggesting hepcidin resistance in this condition [ 37 ]. Nevertheless, it is unknown if the iron loading seen in up to one-third of patients with NAFLD is a consequence of the altered lipid metabolism, or an altered expression of iron-regulatory genes, or a combination of both.…”
Section: Discussionmentioning
confidence: 99%
“…Also, bone morphogenic protein-binding endothelial regulator [ 34 ] and hepatocyte nuclear factor-4alpha [ 35 ] have been reported to influence iron absorption, and in mice, a high fat diet by itself could increase iron absorption [ 36 ]. An impairment in the ability of hepcidin to inhibit iron absorption was demonstrated in DIOS, suggesting hepcidin resistance in this condition [ 37 ]. Nevertheless, it is unknown if the iron loading seen in up to one-third of patients with NAFLD is a consequence of the altered lipid metabolism, or an altered expression of iron-regulatory genes, or a combination of both.…”
Section: Discussionmentioning
confidence: 99%
“…Iron-load is present in 1/3 of the patients with NAFLD and is a risk factor for progressive liver damage, especially when NAFLD is part of DIOS. In DIOS there is an adequate increase in hepcidin levels in response to iron-load, but the increase in hepcidin levels cannot control the rise in transferrin saturation (TS), suggesting a hepcidin-resistant state (Rametta et al 2016 ). It remains to be seen how could these changes affect iron-load in the liver and the tendency towards liver fibrosis.…”
Section: Mechanisms Of Low Hepcidin In Liver Diseasementioning
confidence: 99%
“…Indeed, DIOS and NAFLD disorders show elevated hepcidin levels related to hyperferritinemia. To confirm this hypothesis, we have recently demonstrated that iron challenge in iron-depleted DIOS patients did not restrain iron absorption despite adequate hepcidin production, suggesting that hepcidin resistance (i.e., the impaired hepcidin activity) and not the deficit of hormone production is involved in DIOS pathogenesis [81].…”
Section: Insulin Resistance and Iron Homeostasismentioning
confidence: 95%